Karakterisasi morfologi kakao (Theobroma Cacao L.) klon harapan tahan VSD di Puslitkoka Jember - Ilyas, M Ramadloni (Maliki Interdisciplinary Journal, 2023)
Cocoa (Theobroma cacao L.) is one of the national scale plantation commodities and plays an important role for the Indonesian economy. Success in cocoa propagation can be realized by taking into account several factors, one of which is VSD (Vascular Streak Dieback). Puslitkoka Jember has succeeded in finding VSD resistant cocoa clones including KW 617, KW 604, KW 733, KW 606, HKW 6/17, KWN II/1/5, KWN II/2/1, KWN II/10/5, and KWN II/14/13. Characterization provides added value in enriching gene diversity and forming new diversity for better production and disease resistance. This research is a non-experimental study which was conducted in a survey with a purposive sampling method. Sampling was carried out on cocoa clones that entered the productive age around the age of 5-10 years. The results were analyzed descriptively qualitatively and quantitatively which were generally based on the Catalog of Cacao Clones guidelines. Cluster analysis was performed using the Multi Variation Analysis System (NTSYS) version 2.02 software. The results showed that all hopeful cocoa clones had various characters, ranging from leaves, flowers and fruit. The results of the clustering analysis obtained a similarity value of 48-75% which were grouped into 3 clusters. Cluster I has a flower stalk length of ≥ 15 mm as the main feature, cluster II has a rather rough fruit texture as the main feature, while cluster III has a medium depth of fruit groove as the main feature.